SIMULASI PENGGUNAAN FILTER AKTIF SHUNT DENGAN KONTROL PI UNTUK MEREDAM TOTAL HARMONIC DISTORTION (THD) PADA GEDUNG DH TEKNIK ELEKTRO UNIVERSITAS UDAYANA - Kresna Dharma Yudha, A.A. Gede; Indra Partha, Cok. Gede; Sukerayasa, I Wayan (Program Studi Teknik Elektro UNUD, 2023)
Every daily activity requires electrical energy. Electrical energy loads vary. Harmonic distortion is one of the results of current and voltage wave disturbances caused by non-linear loads, such as lamps, computers, and air conditioners, among others. This causes a decrease in the quality of electric power. High resonance disturbances can cause increased harmonics which can reach 4 to 10 times under full charge conditions. One way to overcome harmonic disturbances is by using a harmonic filter. In this study, an active shunt filter with PI control is used to reduce harmonic resonance disturbances. The THD value according to the IEEE 519-2014 standard is obtained by using this harmonic filter. In this study using Matlab Simulink simulation software. The THD obtained before the simulation was carried out, namely THDv in the R phase = 1.62%, S = 1.64%, T = 1.71%, THDi in the R phase = 14.73%, S = 12.96%, T = 13.53%. The THD obtained after the simulation is THDI at each phase R = 3.29%, S = 3.01%, T = 4.53%.